Algorithms and Data Structures 14th International Symposium, WADS 2015, Victoria, BC, Canada, August 5-7, 2015. Proceedings - Dehne, Frank; Sack, Jörg-Rüdiger.; Stege, Ulrike; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 14th Algorithms and Data Structures Symposium, WADS 2015, held in Victoria, BC, Canada, August 2015. The 54 revised full papers presented in this volume were carefully reviewed and selected from 148 submissions. The Algorithms and Data Structures Symposium - WADS (formerly Workshop on Algorithms And Data Structures), which alternates with the Scandinavian Workshop on Algorithm Theory, is intended as a forum for researchers in the area of design and analysis of algorithms and data structures. WADS includes papers presenting original research on algorithms and data structures in all areas, including bioinformatics, combinatorics, computational geometry, databases, graphics, and parallel and distributed computing.
Contact Graphs of Circular Arcs -- Contact Representations of Graphs in 3D -- Minimizing the Aggregate Movements for Interval Coverage -- Online Bin Packing with Advice of Small Size -- On the Approximability of Orthogonal Order Preserving Layout Adjustment -- An Optimal Algorithm for Plane Matchings in Multipartite Geometric Graphs -- Generation of Colourings and Distinguishing Colourings of Graphs -- Strictly Implicit Priority Queues: On the Number of Moves and Worst-Case Time -- On Coct-Free Multi-Coloring -- Semi-dynamic connectivity in the plane -- Interval Selection in the Streaming Model -- On the Bounded-Hop Range Assignment Problem -- Greedy Is an Almost Optimal Deque -- A New Approach for Contact Graph Representations and Its Applications -- Communication and Dynamic Networks -- Dealing With 4-Variables by Resolution: An Improved MaxSAT Algorithm -- Select with Groups of 3 or 4 Approximating Nearest Neighbor Distances -- Linearity is Strictly More Powerful than Contiguity for Encoding Graphs -- On the Complexity of an Unregulated Traffic Crossing -- Finding Pairwise Intersections Inside a Query Range -- Cache-Oblivious Iterated Predecessor Queries via Range Coalescing -- Polylogarithmic Fully Retroactive Priority Queues -- On the Minimum Eccentricity Shortest Path Problem -- Convex polygons in geometric triangulations -- Straight-line Drawability of a Planar Graph Plus an Edge -- Solving Problems on Graphs of High Rank-Width -- The Parametric Closure Problem -- Rooted Cycle Bases -- On the Chain Pair Simplification Problem -- Finding Articulation Points of Large Graphs in Linear Time -- LP-based Approximation Algorithms for Facility Location in Buy-at-Bulk Network Design -- Universal Reconstruction of a String -- The complexity of dominating set reconfiguration -- Editing Graphs into Few Cliques: Complexity, Approximation, and Kernelization Schemes -- Competitive Diffusion on Weighted Graphs -- Sorting and Selection with Equality Comparisons -- Polynomial Delay Algorithm for Listing Minimal Edge Dominating sets in Graphs -- Fast and simple connectivity in graph timelines -- Dynamic Set Intersection -- Time-Space Trade-of is for Triangulations and Voronoi Diagrams -- A 2k-Vertex Kernel for Maximum Internal Spanning Tree -- Reconfiguration on sparse graphs -- Smoothed Analysis of Local Search Algorithms -- Optimal Shue Code with Permutation Instructions -- Non-Preemptive Scheduling on Machines with Setup Times -- A Moderately Exponential Time Algorithm for k -IBDD Satisfiability -- On the Parameterized Complexity of Girth and Connectivity Problems on Linear Matroids -- Inferring People's Social Behavior by Exploiting Their Spatiotemporal Location Data -- lastic Geometric Shape Matching for Point Sets under Translations -- Constant Time Enumeration by Amortization -- Computing the Center of Uncertain Points on Tree Networks -- Swapping Colored Tokens on Graphs.
Keywords: Algorithms; Data structures (Computer science).; Computer science—Mathematics.; Computer graphics; Numerical analysis; Computer communication systems; Algorithm Analysis and Problem Complexity; Data Structures; Discrete Mathematics in Computer Science; Computer Graphics; Numeric Computing; Computer Communication Networks